The Effect of Employee Satisfaction on Remuneration on the State Civil Apparatus (ASN) Engagement at the Personnel Bureau of the Supreme Court of the Republic of Indonesia - Ailsa Azzahri; Eddy Kusponco Wibowo; Arifiani Widjayanti (Countable (Contemporary Business and Sustainability Science), 2025)
Employee engagement is a management strategy that influences the achievement of organisational goals and objectives. Achieving organisational success requires a high level of commitment. This is because it is important to encourage high-performance contributions from employees. This study employed a descriptive quantitative approach to investigate the impact of employee satisfaction on remuneration on engagement. The study focuses on the Personnel Bureau at the Supreme Court of the Republic of Indonesia, using a sample of 72 ASN employees. The indicators cover seven dimensions of employee engagement and have been adapted for the Indonesian context, including both the private and public sectors, making them more suitable for testing in the public sector. A simple linear regression test via the SPSS program was used to prove that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. There is a significant effect of employee satisfaction on remuneration and on employee engagement, as the value of 0.000 is significantly less than 0.05. Employee satisfaction influences employee engagement to the extent of 52.5%, while 47.5% is influenced by other variables or factors not included in this study.